Office of the Dean, College of Social Sciences and Philosophy Records Management Policy a project proposal - Gerodias, Sheryl T.; Golfo-Barcelona, Mary Grace, P.; Lagrama, Eimee Rhea, C. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2018)
The College of social Sciences and Philosophy (CSSP) is one of the largest colleges in the University of the Philippines Diliman. It is composed of 9 departments: Anthropology, Geography, History, Linguistics, Philosophy, Political Science, Psychology, Sociology and Population Institute. There are 7 offices under the Office of the Dean, namely, Office of the College Secretary, Office of the Associate Deans for Academic Affairs, Office of the Associate Dean for Research and Publications, Office of the Associate Dean for Administrative and External Affairs. Graduate Program Office of Student Affairs, and Office for Student Learning Outreach-Pahinungod. All of these offices creating records, and some records are forwarded to the Office of the Dean such as personnel records or 201 Files. Filing of records has been part of the daily routine of the personnel in charge of records of the Office of the Dean. These records should be accessible anytime they are needed. A records management policy with file plan, and records retention and disposition schedule (RRDS) are effective tools in records management. With these tools, the office can do effective records management practices. The office will not just meet legal requirements but will benefit in many ways such as uniformity of filing system, access to/retrieval of, safeguarding/security, and preservation of records. Every office must have these tools, especially government offices.
The study observed several problems that need to be addressed and made known by the Dean. These include insufficient knowledge of the two (2) personnel in charge of records, filing system, storage, and preservation practices. Based on RA 9470, there are certain requirements that need to be complied with such as appointment of a records officer, establishing a mini storage or archives and many more of that sort.
The outputs of this study include the records management policy, file plan, and records retention and disposition schedule. These tools will help the office to avoid problems in the future and aid in knowing and owning its responsibilities and authorities.
It is recommended that the office of the Dean of CSSP create a Records Management Committee who will formulate the records management policy. The records management policy's goal is to create and organize authentic, reliable, complete and usable records, whether permanent or temporary, according to their functions. This policy is also established to provide a uniform and standard classification scheme and will define the responsibilities of the records officer and authorities. Additionally, it will also serve as reference to new staff or employees.
Special Problem (Master of Library and Information Science)
Keywords: Records management; College of Social Sciences and Philosophy, Office of the Dean -- Records management